Analysis of Protein Separation Mechanism in Charged Ultrafiltration Membrane - Ariono, Danu; Aryanti, Putu Teta P.; Wardani, Anita Kusuma; Wenten, I Gede (Journal of Engineering and Technological Sciences, 2018)
The separation mechanism of proteins on a charged ultrafiltration membrane was analyzed using the extended NernstâPlanck (N-P) model. The model was solved numerically based on experimental data during ultrafiltration of bovine serum albumin/BSA and hemoglobin at various pH (between 5 and 8) to obtain the flux parameter (Jv). The flux parameter was used to determine the effective charge of the membrane (f) and the actual membrane porosity (Ak). These two parameters were then used to predict the transport mechanism of proteins through the charged membrane. Higher flux was obtained during the ultrafiltration of BSA compared to hemoglobin. The most effective separation of mixed proteins occurred at pH 5 (aalbumin= 5). In addition, the mobility of a single protein was lower than when it was mixed with other proteins that had different charges. The effective charges of the membranes were varied between 0.99996 to 1.0000, which means that the fixed charge on the membrane structure was higher than the concentration of proteins, thus the effective charge of the membrane was not influenced by the presence of protein charge at various pH. On the contrary, the value of Ak was influenced by the type and charge of the proteins. A decrease of negative charge along with an increase of solution pH increased the porosity of the membrane, thus reducing the rejection of proteins.